(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
This study aims to evaluate the factors influencing the success of the transition to electronic payment systems in Iraqi banks and to analyze the relationship between the adoption of electronic payment systems and the extent to which the adoption of these systems affects the reduction of operating costs without affecting the quality of services provided by them. The importance of this study stems from the accelerated shift towards digitization in the financial field and supporting national trends towards the transition to a non-cash economy. The study adopted the null hypothesis that there is no statistically significant effect of adopting electronic payment systems in reducing operating costs in Iraqi banks. The study adopted the descriptive analytical approach to explain the problem and the relationships between its elements by collecting financial data for a sample of Iraqi banks for the period (2020-2024) and deriving financial ratios that represent the study variables. The study reached several results, the most important of which is the lack of an effect of adopting electronic payment systems in reducing operating costs in Iraqi banks, despite the good level of application of electronic payment systems by these banks, with a positive correlation between the level of adoption of electronic payment systems. The level of operational costs, and the study presented several recommendations, including updating cost systems to be consistent with the nature of the digital transformation in the use of payment systems, enhancing awareness campaigns and customer confidence to expand the base of use of electronic payment methods, and updating electronic payment systems periodically to avoid technical failures and maintain cyber security.